CHANGES LYMPH FLOW, HEART AND TRANSCAPILLARY EXCHANGE FLUID AND PROTEINS REFLEX-HUMORAL INFLUENCES - N., Myrzakhanov; N., Myrzakhanova M. (European Scientific Journal, ESJ, 2013)
This report presents the results of a study lymph, lymph pressure, heart, arterial and venous pressure, state transcapillary exchange of fluid and protein in normal and correlation analysis. In addition, data on changes in the heart and lymph flow if the pressure in the lymphatic vessels and with intramuscular kallekreina. To study the reflex influences of lymphatic vessels to the lymph vessels and the heart of chronic experiments were carried out in 26 sheep with lymph-venous anastomosis and the catheter according to our methodology. We have also revealed the presence of interceptive reflexes and set intralymphatics reflex effect of receptor lymph vessels in the heart. Thus, these data suggest that each region of the body and the body as a whole is determined by multiparametric lymph circulation relationship between different functional systems (lymph, blood, heart activity, the state of biological barriers), providing homeokinesis.